а) sin∝*cos∝*ctg∝=sin∝*cos∝*cos∝/sin∝=cos²∝
использовал формулу ctg∝=cos∝/sin∝
б) tgx*ctgx*cos²x=cos²x
использовал формулу tgx*ctgx=1
в) (1-cos∝)*(1+cos∝)=1-cos²∝=sin²∝
г) sin²∝*ctg²∝/(1-sin²∝)=cos²∝/cos²∝=1
использовал формулу ctg²∝*sin²∝=cos²∝
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а) sin∝*cos∝*ctg∝=sin∝*cos∝*cos∝/sin∝=cos²∝
использовал формулу ctg∝=cos∝/sin∝
б) tgx*ctgx*cos²x=cos²x
использовал формулу tgx*ctgx=1
в) (1-cos∝)*(1+cos∝)=1-cos²∝=sin²∝
г) sin²∝*ctg²∝/(1-sin²∝)=cos²∝/cos²∝=1
использовал формулу ctg²∝*sin²∝=cos²∝